How to conduct a psychic session - Edward, John (John J.) (Edgewood, NY : Ingenious Designs LLC, 2007)
Teaches the tools and awareness for psychic ability.
DVD 6. How to conduct a psychic session --
DVDs.
107387
Keywords: Edward, John; Spiritualism